CT features predict tumour invasion of adrenal pheochromocytoma: a retrospective observational study - Sisi Zheng; Rongli Xie; Boke Liu; Jingjing Jiang; Mengsu Zeng; Yuan Ji; Mingliang Wang (BMC Medical Imaging)
Abstract Objective To investigate the predictive value of the CT features of adrenal pheochromocytoma (PCC) for invasive behaviour. Methods From November 2009 to December 2021 at Zhongshan Hospital Affiliated with Fudan University, the clinical and CT data of 148 patients with 163 lesions confirmed by surgery and pathology were retrospectively analysed. The cases were divided into an invasive group and a noninvasive group on the basis of the surgical and pathological results; 27 lesions in 26 patients were classified into the invasive group, whereas 136 lesions in 122 patients were classified into the noninvasive group. Clinical data such as patient age, sex, clinical symptoms, intraoperative blood pressure fluctuations and CT data such as the mean lesion diameter, shape, boundary, calcification, streak sign, and necrosis/cystic degeneration area were compared between the two groups. The density of the solid components of the lesions in the nonenhanced image, arterial phase, and venous phase were measured, and the degree of enhancement, percentage and difference in the degree of enhancement in the different phases were calculated and compared between the two groups statistically. Results There were statistically significant differences in the mean diameter, shape, border, streak sign, and tumour blood vessels between the invasive group and the noninvasive group (P < 0.05). There was no significant difference in tumour calcification, the proportion or distribution of necrosis/cystic degeneration, or the fluid level in cystic degeneration between the two groups (P > 0.05). There were significant differences in the density and degree of enhancement of the solid component of the tumour in the arterial phase and venous phase, as well as the percentage of enhancement in the venous phase, between the two groups (P < 0.05). There were no significant differences in the density of the solid components of the tumour on nonenhanced images, the degree of enhancement between the arterial phase and the venous phase, or the percentage of enhancement of the lesions in the arterial phase (P > 0.05). The areas under the ROC curves of the arterial-phase density, venous-phase density, arterial-phase enhancement degree, venous-phase enhancement degree, and venous-phase enhancement percentage were 0.618, 0.641, 0.618, 0.639, and 0.635, respectively. The density, enhancement degree and enhancement percentage of the venous phase can be used for discrimination. Conclusion Pheochromocytoma with unclear borders, visible tumour blood vessels, and enhancement with the streak sign has predictive value for invasive behaviour, whereas a greater degree of enhancement of the solid component indicates that the tumour has no invasive behaviour.